1989
DOI: 10.1128/mcb.9.12.5702
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative transcriptional control by heme of genes encoding 3-hydroxy-3-methylglutaryl coenzyme A reductase in Saccharomyces cerevisiae.

Abstract: Responses of the yeast genes encoding 3-hydroxy-3-methylglutaryl coenzyme A reductase, HMGI and HMG2, to in vivo changes in heme concentrations were investigated. Expression of the genes was determined by direct measurement of the mRNA transcribed from each gene, by direct assay of the enzyme activity encoded by each gene, and by measurement of the expression of lacZ fusions to the control regions of each gene. These studies indicated that expression of HMGI was stimulated by heme, whereas expression of HMG2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 55 publications
2
85
1
Order By: Relevance
“…28 However, these studies were conducted before the demonstration of two isoforms of the enzyme. Thorsness et al 259 have found that HMG1 expression was stimulated by heme while HMG2 expression was inhibited, again indicating a relationship between heme and sterol biosynthesis.…”
Section: Sterol Biosynthesis: Acetate To Farnesyl Pyrophosphatementioning
confidence: 99%
“…28 However, these studies were conducted before the demonstration of two isoforms of the enzyme. Thorsness et al 259 have found that HMG1 expression was stimulated by heme while HMG2 expression was inhibited, again indicating a relationship between heme and sterol biosynthesis.…”
Section: Sterol Biosynthesis: Acetate To Farnesyl Pyrophosphatementioning
confidence: 99%
“…Microscopic examination revealed that the inviable spores did not germinate. We therefore conclude that the Cells were lysed by vortexing in the presence of glass beads (Thorsness et al, 1989) and a 50-70% (NH 4 ) 2 SO 4 fraction was used as the source of enzyme (Hossain and Kallenbach, 1974). The kinetics of tRNA-dependent incorporation of 3 H-labeled tryptophan (TRP) into trichloroacetic acid-insoluble material was measured as a function of protein (Yesland and Johnson, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Hem14p converts protoporphyrinogen IX to protoporphyrin IX in the late step of heme synthesis (28,29), so in ⌬hem14 cells, the function of heme-containing proteins such as the ergosterol synthesis-related enzymes Erg5p and Erg11p (36,37) would be reduced. Moreover, the expression of HMG1 and ERG11, regulated by heme at the transcriptional level (32,33), would be also decreased. Finally, Kes1p, an oxysterol-binding protein homolog, is thought to be involved in ergosterol transport from the Golgi to the plasma membrane, and although total ergosterol levels in ⌬kes1 cells are unchanged, the levels on the cell surface are reduced (38).…”
Section: Discussionmentioning
confidence: 99%
“…Hmg1p is involved in the synthesis of farnesyl diphosphate (30), which is also required for synthesis of certain hemes (hemes O and A) (31). Some genes involved in ergosterol biosynthesis, including HMG1 and ERG11, are regulated by heme at the transcriptional level (32,33), and the transcription factor Hap1p is known to be involved in this regulation (34).…”
Section: Phs Sensitivity In the Mutants Of Identified Genes-wementioning
confidence: 99%